Digital Games (Gamification) in Learning and Training: an Approach to Adaptation and Integration in the Classroom (GIST – Education and Learning Research Journal, 2020)
This article is the result of the SGI 2174 project. Its objective is to identify how elements, techniques and mechanics game (gamification) have been implemented, as an ICT-mediated learning strategy for learning and training in the education. A systemic literary review of works on the subject is carried out to contextualize and identify methods, techniques, tools and platforms of gamification.  The results make an analysis of the articles reviewed, and describe and describe the technologies and methodologies of gamification and the most relevant results with which gamification has been implemented in educational and business environments. This project is developed in the research groups TelemaTICs and TICA, and funded by DIN-UPTC
Keywords: learning and technology; education and ICT; e-learning; gamification; adaptation; integration; classroom; business environments